Microbial synthesis of a novel terpolyester P(LA‐co‐3HB‐co‐3HP) from low‐cost substrates. Issue 2 (17th November 2016) - Ren, Yilin; Meng, Dechuan; Wu, Linping; Chen, Jinchun; Wu, Qiong; Chen, Guo‐Qiang
Summary: Polylactide (PLA) is a bio‐based plastic commonly synthesized by chemical catalytic reaction using lactic acid (LA) as a substrate. Here, novel LA‐containing terpolyesters, namely, P[LA‐ co ‐3‐hydroxybutyrate (3HB)‐ co ‐3‐hydroxypropionate (3HP)], short as PLBP, were successfully synthesized for the first time by a recombinant Escherichia coli harbouring polyhydroxyalkanoate (PHA) synthase from Pseudomonas stutzeri (PhaC1 Ps ) with 4‐point mutations at E130D, S325T, S477G and Q481K, and 3‐hydroxypropionyl‐CoA (3HP‐CoA) synthesis pathway from glycerol, 3‐hydroxybutyryl‐CoA (3HB‐CoA) as well as lactyl‐CoA (LA‐CoA) pathways from glucose. Combining these pathways with the PHA synthase mutant phaC1 Ps (E130D S325T S477G Q481K), the random terpolyester P(LA‐ co ‐3HB‐ co ‐3HP), or PLBP, was structurally confirmed by nuclear magnetic resonance to consist of 2 mol% LA, 90 mol% 3HB, and 8 mol% 3HP respectively. Remarkably, the PLBP terpolyester was produced from low‐cost sustainable glycerol and glucose. Monomer ratios of PLBP could be regulated by ratios of glycerol to glucose. Other terpolyester thermal and mechanical properties can be manipulated by adjusting the monomer ratios. More PLBP applications are to be expected. Abstract : Here, novel LA‐containing terpolyesters, namely, P[LA‐co‐3‐hydroxybutyrate (3HB)‐co‐3‐hydroxypropionate (3HP)], short as PLBP, were successfully synthesized for the first time by a recombinant Escherichia coli harbouring polyhydroxyalkanoate (PHA) synthase from Pseudomonas stutzeri (PhaC1Ps) with 4‐point mutations at E130D, S325T, S477G and Q481K, and 3‐hydroxypropionyl‐CoA (3HP‐CoA) synthesis pathway from glycerol, 3‐hydroxybutyryl‐CoA (3HB‐CoA) as well as lactyl‐CoA (LA‐CoA) pathways from glucose. Combining these pathways with the PHA synthase mutant phaC1Ps (E130D S325T S477G Q481K), the random terpolyester P(LA‐co‐3HB‐co‐3HP) or PLBP, was structurally confirmed by nuclear magnetic resonance (NMR) to consist of 2 mol% LA, 90 mol% 3HB and 8 mol% 3HP respectively. Remarkably, the PLBP terpolyester was produced from low‐cost sustainable glycerol and glucose. Monomer ratios of PLBP could be regulated by ratios of glycerol to glucose.